New Treatment Strategies against Hepatitis C Viral Infection - Marc Bilodeau; Daniel Lamarre (Canadian Journal of Gastroenterology)
Treatment of hepatitis C virus infection is currently based on a combination of pegylated interferon and ribavirin. Because efficacy of this therapy remains suboptimal and side effects sometimes problematic, major efforts have been put forward by scientists and the pharmaceutical industry to develop alternative treatments for this chronic infection. Over the past few years, clinical studies performed with some of these new agents have been presented at major international meetings. The present paper aims to review the rationale underlying the development of these new forms of treatment as well as the current available data concerning their clinical efficacy.